The Effectiveness of Inquiry Based Instructions Module on Excretory System Material to Improve Student Learning Outcomes in 11th Grade Science Senior High School - Tanaya, I Nyoman Tri Bayu; Suciati, Suciati; Maridi, Maridi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
Learning outcomes have three domains that consist of cognitive, affective and psychomotor, important part of a learning process to determine the level of learning objectives. This research aims to determine the effectiveness of inquiry based instructions module on the material excretion system on student learning outcomes consist of cognitive, affective and psychomotor in 11th Grade Science Class of Senior High School. This research uses a learning model that has never been used, namely by using the syntax of the inquiry based instruction model. Researcher used quasi experimental research and pre-test and posttest control group design for the research design in this paper. The samples of this study are 36 students of 11th Grade Science Class 4 as experimental class using module and 36 students of 11th Grade Science Class 6 as control class using lecture method. Data were collected using a 30-item multiple-choice test technique and they were analyzed by t-test using SPSS. The results show that the t-test in the experimental class was obtained by probability (p) 0.00 (p <0.05), so H0 was rejected. The results of the analysis show that there is a significant difference between the pretest and posttest score of the students using a module with gain scoring of 0.45. The learning outcomes in the control class also improved but not as large as the gain scoring in the experimental class of 0.24. It can be concluded that the inquiry based instruction module on the effective excretion system material improves students' learning outcomes in 11th Grade Science Class of Senior High School.